(3eG jYhd Ydjg aj GdeVGa hGdeVGa Edjgs - (3eMeO Cejf Hf aVd Gddg Hf eMH Gddg Hf eMeO GdeMHj GdMehj, eMH GdOjf , CHh HcQ,J (B1111 (3g` s
(3ChdgG (B:s
(3MeO Gddg JYGdi faSg CLd eG jYhd Ydjg CeG HYO ajbhd GdYHO GdMbjQ de CRd CLhH QjGV GdCOH aCLfi TGQgG GdWQjI Yf cKH s
(3BNQgG (B:s
(3hbGd BNQ hCjGe cCjGe GdTHGH bGd eDdag HQO Gddg eVLYg bO Je GdcJGH HYhf Gdedc GdhgGH s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3fSNI efbhdI Yf fSNI HNW GdeUfa aQZ efgG SfI (B1109 s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B41 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B78s
(3JHUQGJ GdCUd (B:s
Keywords: (3GddZIs